Gambaran Faktor Psikososial dan Gejala Stres Kerja pada Karyawan Kantor Proyek Pembangunan X - Putri, Vania Widyadhari Haris; Kurniawidjaja, L. Meily (UI Scholars Hub, 2022)
This study aims to describe the perception of workers on psychosocial factors and to find out the symptoms of occupational stress among the staff. The dependent variables are occupational stress symptoms, while the independent variables are individual characteristics, context to work, and content of work. The research design is cross sectional, using online questionnaire and involving all 51 employees. Univariate analysis is using computer software. Perception of psychosocial factors refers to the average score, 1.00-3.00 is poor and 3.01-5.00 is good. The results showed psychosocial factors in context to work were perceived as poor, namely decision latitude and control (2.92) and home-work interface (2.34), while content of work perceived as poor, namely work environment (2.21), workload and work pace (2.63), and work schedule (2.03). Occupational stress level refers to the average score, 1.00-2.33 is mild, 2.34-3.67 is moderate, and 3.68-5.00 is high. Occupational stress symptoms that manifested on physical, psychological, cognitive, and behavioral are classified as mild with average score 2,14; 2.22; 2.33; and 2.0 respectively, and occupational stress that were classified as moderate-high were experienced by 33.3%, 47.1%, 45.1%, and 36.3% respectively. Overall, the psychosocial factors is classified as poor with complaints of mild occupational stress symptoms.